2020
DOI: 10.3390/polym12040754
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/PAMAM/Hydroxyapatite Engineered Drug Release Hydrogels with Tunable Rheological Properties

Abstract: In this paper, a new formulation of biodegradable and bioresorbable chitosan-based hydrogel for controlled drug release was investigated. A chitosan–dendrimer–hydroxyapatite hydrogel, obtained by covalently grafting chitosan powder with an hyperbranched PAMAM dendrimer followed by in-situ precipitation of hydroxyapatite and gelification, was synthesized and characterized by FTIR, NMR, TGA, XRD and rheological studies. The hydrogels have been also doped with an anti-inflammatory drug (ketoprofen) in order to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Chemical co-precipitation represents a facile method to synthesize tunable HAp-based biomaterials, starting from calcium and phosphorous precursors and conveniently adjusting various reaction parameters (temperature range, pH value, nature, and type of templating agent) [ 85 , 86 ]. Moreover, this versatile approach is suitable for extending the bioactivity and biofunctionality of HAp by doping with various inorganic ions [ 87 , 88 ] and by obtaining apatite composites [ 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical co-precipitation represents a facile method to synthesize tunable HAp-based biomaterials, starting from calcium and phosphorous precursors and conveniently adjusting various reaction parameters (temperature range, pH value, nature, and type of templating agent) [ 85 , 86 ]. Moreover, this versatile approach is suitable for extending the bioactivity and biofunctionality of HAp by doping with various inorganic ions [ 87 , 88 ] and by obtaining apatite composites [ 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the BMP-2 release rate was relatively slow in the case of HAP/Col hydrogel (200/3.8). This is because the degree of hydration and the subsequent degradation of collagen fiber are retarded by HAPs, delaying degradation and slowing the DR kinetics. , It is to be noted that a steep change of relative Δ E occurred for the HAP/Col hydrogel (200/3.8) because the HAP detachment from the hydrogel induces its porous structure, which changes the indentation behavior. , In contrast, in the case of the HAP/Col hydrogel (100/3.8), the porous structure of the hydrogel was less affected by HAP detachment compared to that of the HAP/Col hydrogel (200/3.8), as shown in Figure c. These results indicated that adding an appropriate amount of HAPs into hydrogels plays a crucial role in determining their degradation rate and DR profiles.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the drug release from hydrogels is governed by several phenomena: diffusion, erosion, network relaxation, all in various proportions, depending on the polymer nature, network stability and parameters, morphology, hydrophilicity, the nature of the drug and its interaction with the matrix, the release medium etc., [ 37 , 38 , 39 , 40 ]. In order to study the drug release kinetics and mechanism, the drug release data were fitted into four models, using the following equations [ 21 , 41 , 42 , 43 ]: where Q t is the amount of drug released at time t, Q 0 is the original drug concentration in the material (40 mg), n is the release exponent and K is the release rate constant.…”
Section: Resultsmentioning
confidence: 99%